The Effect of Project Based Learning Model on Learning Outcomes of Pancasila and Civic Education of State Vocational High School Students 1 Rambah, Rokan Hulu Regency - Rani Namira; Jumili Arianto; Mirza Hardian (CV. Rayyan Dwi Bharata, 2023)
The use of less effective and efficient learning methods (conventional learning methods) with low student participation has an impact on student learning outcomes, low student interest in learning, students have difficulty concentrating in listening to explanations of material presented by the teacher. The purpose of this study was to determine the learning outcomes of PPKn students who were taught using a project-based learning model (PJBL) and without using a project-based learning model (PJBL) and to determine whether there was any influence of project-based learning models on student learning outcomes. This type of quantitative research is a quasi-experimental design with a pretest-posttest control group design. Data collection techniques are observation, tests and documentation. The population is class XI with a sample of 70 students. Obtained tcount = 5.926 ttable = 199547, so there is an influence of the Project Based Learning learning model on student learning outcomes